A decision tree approach to screen drinking water contaminants for multiroute exposure potential in developing guideline values. (3rd July 2017) - Krishnan, Kannan; Carrier, Richard
ABSTRACT: The consideration of inhalation and dermal routes of exposures in developing guideline values for drinking water contaminants is important. However, there is no guidance for determining the eligibility of a drinking water contaminant for its multiroute exposure potential. The objective of the present study was to develop a 4-step framework to screen chemicals for their dermal and inhalation exposure potential in the process of developing guideline values. The proposed framework emphasizes the importance of considering basic physicochemical properties prior to detailed assessment of dermal and inhalation routes of exposure to drinking water contaminants in setting guideline values.